Land Use and Cover Changes versus climate shift: Who is the main player in river discharge? A case study in the Upper Paraná River Basin. (1st May 2022) - Abou Rafee, Sameh A.; Uvo, Cintia B.; Martins, Jorge A.; Machado, Carolyne B.; Freitas, Edmilson D.
Abstract: Assessing the relative contribution of Land Use and Cover Changes (LUCC) and climate changes on runoff still represents a great challenge for water resources management. This issue is particularly critical for the Upper Paraná River Basin (UPRB), one of the most important basins in South America and responsible for most of the production of food, ethanol, and electricity generation in Brazil. In this paper, we used the Soil and Water Assessment Tool (SWAT) to quantitatively assess the relative contribution of both forcings. The simulation period included a time of great importance for climate studies, known as the 1970s global climate shift, and of great impact on river discharge within the UPRB. Three land use and cover scenarios were assigned to the 1961–1990 period of simulations, representing land use and cover during a pristine period (around the Year 1500), 1960, and 1985. Thirteen years of precipitation before and after the climate shift (considered to be the period 1974–1977) were analyzed and compared. Results showed a precipitation increase for the basin in general after the climate shift. The increase in rainfall reached up to 15% in many northern areas and more than 20% in the southern parts of the basin. By comparing all simulations, results indicate that both LUCC and precipitation increase due to the climate shift had a significant effect on the changes in annual discharge of the largest rivers of the UPRB. However, the results suggest that the impact of the precipitation increase on the discharge exceeded that of the LUCC. Between 1960 and 1985 the LUCC accounts for about 16% of the increase of the median annual discharge, whereas climate shift accounts for an increase of about 32%. These findings, suggesting a more relevant role for the climate, are consistent with two recent water crisis experienced by the country in the last decades, caused by prolonged below-normal rainfall throughout 2001/2002 and again in 2014/2015. Graphical abstract: Image 1 Highlights: We simulated land use and cover from a pristine period (Year 1500), 1960, and 1985. We evaluated the effects of precipitation change on discharge from 1961 to 1990. Natural vegetation fell by more than half of the original area up to 1985. Precipitation increased by more than 20% after the 1970s global climate shift. Results suggest that climate shift is the main driver in increasing annual discharge.